“Says Who?!” how the Source of Price Information and Affect Influence Perceived Price (Un)fairness - Campbell, Margaret C. (Journal of Marketing Research, 2007)
Three experiments show that the source of price change information—whether human or nonhuman—moderates the effect of price change on perceptions of price fairness. Both inferences of the marketer's motive and stimulus-induced affect mediate the effects of the source and price change. Opportunity and motivation to process also affect the relative influence of inferred motive and affect. This research demonstrates antecedent roles of both price source and affect.